Triskelion-Shaped Hexabenzocoronenes: Synthesis and Characterization of Tris-Substituted HBC Derivatives - Buck, Janina; Hampel, Frank; Hirsch, Andreas (Chemistry - A European Journal, 2025)
The synthesis of unprecedented triskelion-shaped hexa-peri-hexabenzocoronenes with C3, C3h or D3h symmertry is reported. We present a new, five step synthetic access to tris-iodinated HBC derivatives carrying different solubilizing moieties (tert-butyl and mesityl), which serve as suitable building blocks for further functionalization. These molecules can undergo Sonogashira cross coupling reactions to obtain a series of seven ethynyl tris-substituted HBCs. The coupling partners range from carbon-based aromatic scaffolds (tBu-benzene, naphthalene, phenanthrene) to ligands for metal complexes (bipyridine, phenanthroline, terpyridine, acetylacetone). The optoelectronic properties were investigated by UV/vis absorption spectroscopy resulting in a significant bathochromic shift of the absorption maximum compared to the iodinated starting material. Semiempirical calculations were used to determine the conformation and symmetry of the compounds.
CRIS-Team Scopus Importer:2025-02-17
Keywords: C; Hexa-peri-hexabenzocoronene; Sonogashira coupling; tris-substitution; π-extension